330 RISK OF MALNUTRITION AND ITS ASSOCIATION WITH FRAILTY-ASSOCIATED FACTORS IN THE OLDER PERSON. (25th October 2022) - King, L; Donnellan, C; Pillay, I; Sayers, K; Ryan, S; Maher, J
Abstract: Background: The aetiology of malnutrition is multifactorial, with age a facilitating factor. It is associated with poorer physical and mental health and functional ability in frail older persons. Nutritional screening is a key domain in Comprehensive Geriatric Assessment (CGA). This study assessed the relationship between malnutrition risk and other drivers of frailty in the older person by CGA. Methods: All patients who had a CGA completed by an Integrated Care Team for Older Persons from March 2020 to July 2021 inclusive were studied. Data was entered onto an Excel database by a trained administrator. The variables included were: age, gender, swallow screen, living alone, cognition, loneliness, Clinical Frailty Scale (CFS) score, falls history and risk of malnutrition using the Malnutrition-Screening Tool (MST). Odds ratio (OR), 95% Confidence Intervals (CI) was used to determine if there was an association between malnutrition risk and each variable in the total group. Results: In total, 567 patients (325 female, 242 male), mean age 82yrs (SD =19), with median CFS of 6 were studied. Sixty-eight percent (n=384) reported a fall, 37.2% (n=211) had a positive swallow screen, 44% (n=251) lived alone, 35% (n=198) had positive cognitive screening, 14% (n=80) reported loneliness and 31.6% (n=179) were identified as at risk of malnutrition. A positive association was identified between risk of malnutrition and cognitive impairment (OR 1.9, 95%CI 1.2-3.1) and a reported fall (OR 2.2, 95%CI 1.4-3.5). In the population who had a fall and risk of malnutrition, the association remained in those aged ≥80yrs (OR 2.6, 95% CI 1.46 – 4.5) and female (OR 3.6, 95%CI 1.7 – 7.4). Conclusion: The risk of malnutrition is associated with falls risk and cognitive impairment in frail older persons. Frail older persons identified by integrated care team for older persons with falls risk & cognitive impairment will be targeted for specialist dietetic intervention.